A polycatenated hydrogen-bonded organic framework based on embraced macrocyclic building blocks for fluorescence detection of nitrobenzene in water. Issue 9 (13th February 2023) - Zhao, Jin-Qin; Mao, Liang-Liang; Zhang, Guo-Hui; Zhan, Shun-Ze; Xiao, Hongyan; Zhang, Shaoguang; Tung, Chen-Ho; Wu, Li-Zhu; Cong, Huan
Abstract : A polycatenated HOF has been constructed from supramolecular embraced pairs of macrocyclic modules, featuring fluorescent detection of nitrobenzene in water. Abstract : A fluorescent polycatenated hydrogen-bonded organic framework (MEP-HOF) has been developed using a C 3 -symmetric rigid macrocycle as the exclusive building block. Stabilised by intermolecular non-covalent interactions in the solid state, the tri-carboxylated macrocycles form supramolecular embraced pairs which further assemble the interwoven three-dimensional H-bond network with a degree of catenation of seven. The MEP-HOF features easy preparation and regeneration, and its fluorescent properties could be utilised as a sensitive sensor for nitrobenzene detection in water with a detection limit of 61.8 ± 2.2 ppb.